Effect of Dexmedetomidine on Intraoperative Haemodynamics and Postoperative Analgesia in Laparoscopic Cholecystectomy - Trikhatri, Yojan; Singh, Satyendra Narayan; Koirala, Siddhartha; Prasad, Jagat Narayan; Adhikari, Sailesh (Journal of College of Medical Sciences-Nepal, 2018)
Background and objectives: Dexmedetomidine is an α2 agonist with sympatholytic, anxiolytic, sedative and analgesic effect used as adjunct during surgeries for its haemodynamic stabilizing effect and analgesic effect. Primary aims of the study were to evaluate the haemodynamic effect of intravenous dexmedetomidine and the duration and quality of analgesia in laparoscopic cholecystectomy. Secondary aims were sedation levels and occurrence of side effects. Materials and methods: Eighty four patients, American society of Anaesthesiologists physical status I and II, aged 18-60 years of either gender undergoing laparoscopic cholecystectomy in general anaesthesia were randomly allocated into two equal groups. Group C patient received Normal Saline and Group S patient received dexmedetomidine loading dose infusion of 1µg/kg over 10 minutes before induction and maintained with 0.4µg/kg/hr till the removal of gall bladder. Induction with propofol and fentanyl was done. Standard monitoring including Heart Rate, Mean arterial pressure, oxygen saturation were monitored perioperatively. Postoperative analgesia requirement and sedation score were assessed. Results: In Group S, the haemodynamic responses were significantly attenuated. During postoperative period, 24 hours analgesic requirement of diclofenac sodium was 141.43mg in group S as compared to 217.50mg in group C(p<0.001). Side effects were treatable. Sedation was better in Group S. Conclusion: Dexmedetomidine effectively attenuates haemodynamic stress response during laparoscopic surgery with reduction in postoperative analgesic requirements.